2015
DOI: 10.7816/sed-03-02-01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on Learning Styles of Candidate Music Teachers According Various Variables

Abstract: Bu çalışmada müzik öğretmeni adaylarının öğrenme stilleri belirlenmeye ve çeşitli değişkenler düzeyinde değerlendirilmeye çalışılmıştır. Çalışma kapsamında 164 müzik öğretmeni adayına Kolb (1985) tarafından geliştirilen ve Türkçe geçerlik ve güvenirliği Aşkar ve Akkoyunlu (1993) tarafından yapılan "Kolb Öğrenme Stilleri Envanteri" uygulanmıştır. Çalışma sonucunda müzik öğretmeni adaylarının 'değiştiren' ve 'özümseyen' öğrenme stillerini daha çok benimsedikleri, erkek öğrencilerin daha çok 'değiştiren' öğrenme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Several studies were conducted in the field (Altun, Yurga, Zahal, Gürpınar, 2015;Arslan & Babadoğan, 2005;Aşkar & Akkoyunlu, 1993;Babacan, 2010;Baş & Beyhan, 2013;Bozkurt & Aydoğdu, 2009;Demirtaş, 2017;Duman, 2008;Deniz, 2011;Gencel, 2007;Hasırcı, 2006;Kaleli-Yılmaz, Koparan,;Hancı, 2016;Kaya, Bozaslan, Durdukoca, 2012;Kulaç, Sezik, Aşcı, Gürpınar, 2015;Koçak, 2007;Kolb & Kolb, 2005;Kurtuldu & Aksu, 2015;Okay, 2012;Pehlivan, 2010;Süral, 2008;Sarıtaş & Süral, 2010;Şimşek, 2007;Zahal, 2014;) and many researchers developed learning style models. However, previous studies showed that existing learning styles was based on cognitive success of students or they were developed to identify individual differences in a general sense.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were conducted in the field (Altun, Yurga, Zahal, Gürpınar, 2015;Arslan & Babadoğan, 2005;Aşkar & Akkoyunlu, 1993;Babacan, 2010;Baş & Beyhan, 2013;Bozkurt & Aydoğdu, 2009;Demirtaş, 2017;Duman, 2008;Deniz, 2011;Gencel, 2007;Hasırcı, 2006;Kaleli-Yılmaz, Koparan,;Hancı, 2016;Kaya, Bozaslan, Durdukoca, 2012;Kulaç, Sezik, Aşcı, Gürpınar, 2015;Koçak, 2007;Kolb & Kolb, 2005;Kurtuldu & Aksu, 2015;Okay, 2012;Pehlivan, 2010;Süral, 2008;Sarıtaş & Süral, 2010;Şimşek, 2007;Zahal, 2014;) and many researchers developed learning style models. However, previous studies showed that existing learning styles was based on cognitive success of students or they were developed to identify individual differences in a general sense.…”
Section: Introductionmentioning
confidence: 99%